Vocabulary Learning Strategies of a Fluent EFL Learner: A Case Study - Jingga Ameira; Sigit Suharjono (Language and Education Journal, 2026)
Vocabulary knowledge plays a crucial role in EFL learning; however, limited qualitative research has explored how fluent learners apply vocabulary learning strategies in authentic contexts. This study aims to investigate the strategies used by a fluent EFL learner and examine how these strategies reflect cognitive and metacognitive processes based on Schmitt’s taxonomy. A qualitative single-case study design was employed, involving one fluent English learner selected through purposive sampling. Data were collected through a semi-structured interview and analyzed using systematic qualitative procedures. The findings reveal that the participant employed all five categories of vocabulary learning strategies in a flexible and context-dependent manner. Cognitive and metacognitive strategies were more prominent, as reflected in active engagement, contextual learning, and self-regulated learning practices. Vocabulary development was primarily supported by meaningful exposure and communicative use rather than mechanical memorization. These findings highlight the importance of examining fluent learners as information-rich cases to better understand effective vocabulary learning processes. The findings suggest that vocabulary instruction should emphasize authentic language use, strategic flexibility, and learner autonomy in higher education contexts.